Anonymous Sequential Games with General State Space - J. Bergin; D. Bernhardt (Queen's University, Department of Economics, 1991)
In this paper we consider Anonymous Sequential Games with Aggregate Uncertainty. We prove existence of equilibrium when there is a general state space representing aggregate uncertainty. when the economy is stationary and the underlying process governing aggregate uncertainty Markov, we provide Markov representations of the equilibria.
Keywords: 330